PENGARUH CORPORATE ATTRIBUTES TERHADAP ENVIRONMENTAL, SOCIAL, AND GOVERNANCE (ESG) DISCLOSURE - Rizka Aulia Ardhya Garini (2022)
This study aims to determine the effect of market performance, financial performance, foreign ownership, and company risk. The population of this study are ESG Leaders indexed companies. The method used in this research is purposive sampling with a total of 48 research samples. This study uses panel data multiple regression analysis technique and is processed with the help of STATA v.16. The results of this study indicate that the financial performance of foreign ownership has a significant negative effect on Environmental, Social, and Governance (ESG) disclosure. In addition, the market performance and company risk variables have no effect on the Environmental, Social, and Governance (ESG) disclosure.